First surveillance of malaria among seafarers: evaluation of incidence and identification of risk areas: EPIDEMIOLOGY OF MALARIA AMONG SEAFARERS - Pallotta, Graziano; Di Canio, Marzio; Scuri, Stefania; Amenta, Francesco; Nittari, Giulio (Acta Biomedica Atenei Parmensis, 2019)
Malaria is a potentially deadly parasitosis. Due to its geographical distribution, seafarers are particularly exposed to it. This study is an epidemiological analysis on the morbidity of malaria onboard commercial ships without a physician, with the purpose of proposing solutions aimed at limiting further infections in this delicate and difficult working environment. Methods: We examined 17,212 health records of patients embarked on ships assisted by the CIRM from 2011 to 2015. All the diagnosed diseases have been categorized based on the ICD-10 classification system by the WHO. This study analyzed the cases of suspected malaria and the cases of malaria confirmed by clinical tests. The geographical distribution of infections and the drugs chosen by physicians are also assessed. Results: Although a reduction in malaria cases was appreciated during the 5-year period taken into consideration, this disease still covers an important percentage of all infectious diseases that occurred onboard. This proves that it is a major health problem for seafarers. Conclusions: In order to protect seafarers’ population, strengthen malaria prevention and control programs, as well to improve the availability of antimalarial drugs onboard ships is necessary. This may ensure rapid and efficient health interventions in case of need.